(3GdJfhjY GdGbJUGOj aj GdLRGFQ s (3SHd hBdjGJ JYRjR GdUGOQGJ NGQL GdeMQhbGJ s - (3HhdQHGb(B, (3MjGIs ((3GdLRGFQ s (3OGQ CLjGd GdQbej s, 2024)
(3jSYi gPG GdcJGH Edi JbOje YQV hGa hTGed Mhd GdJfhjY GdGbJUGOj hGdJLGQI GdOhdjI heGgj Cge GdGSJQGJjLjGJ GdeJYHI ef WQa GdOhdjI GdLRGFQjI ef CLd GdfghV HGdGbJUGO GdLRGFQj HeG ajg GdGWGQ GdeaGgjej ddJfhjY GdGbJUGOj, YfGUQ GdJfhjY eQGMdg heRjGg, YehejGJ heaGgje Mhd GdJLGQI GdOhdjI hGdJUOjQ , JWhQ GdUGOQGJ GdLRGFQjI NGQL GdeMQhbGJ heDTQGJ bjGS JfGaSjJgG deYQaI GdJfhjY GdGbJUGOj aj GdLRGFQ aj Xd GdGUdGMGJ GdeJNPI ef WQa GdOhdI(B. s
Keywords: (3GdGbJUGOs; (3GdJfejI GdGbJUGOjIs; (3GdeMQhbGJs